Integral sets of quasilinear pulse systems - Akhmetov , M. U.; Perestyuk, N. A. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
We obtain sufficient conditions for the existence of integral sets of a weakly linear system of differential equations with impulse action on surfaces. We study the asymptotic behavior of the solutions beginning on the integral sets and in a neighborhood of these sets.